Comemoração, pobreza e cultura letrada no centenário de Teresina (1952) - Santos, Maurício Feitosa dos (2014)
This paper work intends to discuss the historical break in the speech about poverty in the city of Teresina in the beginning of the 1950’. This period, the city Centennial Anniversary, in 1952, mobilized politicians and intellectuals to think about the city. Mainly the press, to acknowledge the historical character of the Piauí State Capital pauperism was a highlighted aspect by the literate critic in the ephemeris moment. The speeches which permeated literate culture, delimiting the poverty historicity, were prudent regarding to the future. With the occurrence of the 1951-53 draught and the movement of flagellated all over the State and the Capital city, adding the beggars and urban poor population, converged with certain unanimity to interpret those times as a moment of evident crisis. The higher cost of living contributed bluntly to the understanding that the crisis was being aggravated day by day. By the investigation of press chronicles, Demographic Census, Municipal Chambers Minutes and Government Messages, it was possible to trace the general lines in the speech about the crisis and the poverty in the vision of literate. Throughout lawsuits, it was possible to prospect, in perspective, the day by day of common people in that period, seeking to understand the ideas and actions of poor people while claiming their rights.